Evaluasi Pembinaan Manajemen Klub Bola Voli LAPGAS Kota Jambi 2025 - Firdaus, M; Murniati, Sri; Setiawan, Iwan Budi (MAN Insan Cendekia Jambi, 2025)
Management development in a sports club greatly influences the club's growth and achievements. This study aims to evaluate the management development system of the LAPGAS Volleyball Club in Jambi City in 2025, focusing on aspects of organization, training, finance, and athlete development. The study employs a qualitative descriptive method with data collection techniques including interviews, observations, and document studies. The research informants consist of club administrators, coaches, athletes, and other relevant parties involved in sports development in Jambi City. The results indicate that the club's management system has a fairly well-structured organization, but there are still challenges in terms of funding and training facilities. The athlete development program is already running in a structured manner, but improvements are still needed in technology-based training and competition strategy aspects.